How Many Clocks, How Many Times? On the Sensory Basis and Computational Challenges of Circadian Systems - Somers, Jason; Harper, Ross E. F.; Albert, Joerg T. (Frontiers in Behavioral Neuroscience, 2018)
A vital task for every organism is not only to decide what to do but also when to do it. For this reason, ‘circadian clocks’ have evolved in virtually all forms of life. Conceptually, circadian clocks can be divided into two functional domains; an autonomous oscillator creates a ~24h self-sustained rhythm and sensory machinery interprets external information to alter the phase of the autonomous oscillation. It is through this simple design that variations in external stimuli (for example, daylight) can alter our sense of time. However, the clock’s simplicity ends with its basic concept. In metazoan animals, multiple external and internal stimuli, from light to temperature and even metabolism have been shown to affect clock time. This raises the fundamental question of cue integration: how are the many, and potentially conflicting, sources of information combined to sense a single time of day? Moreover, individual stimuli, are often detected through various sensory pathways. Some sensory cells, such as insect chordotonal neurons, provide the clock with both temperature and mechanical information. Adding confusion to complexity, there seems to be not only one central clock in the animal’s brain but numerous additional clocks in the body’s periphery. It is currently not clear how (or if) these ‘peripheral clocks’ are synchronised to their central counterparts or if both clocks ‘tick’ independently from one another. In this review, we would like to leave the comfort zones of conceptual simplicity and assume a more holistic perspective of circadian clock function. Focusing on recent results from Drosophila melanogaster we will discuss some of the sensory, and computational, challenges organisms face when keeping track of time.